Avaliação da relação entre qualidade de sono e uma intervenção com jogos para o desempenho de crianças e adolescentes - Araújo, Danilo de Freitas (2012)
The sleep is an active brain process that allows the efficient realization of daily tasks. The changes on sleep patterns may influence the different cognitive processes performance. Many recent studies show the possibility of cognitive performance improvement, through the cognitive training with the use of computer games. The question is if these interventions may be influenced by the sleep quality. Thus, we evaluated the sleep quality effect about the efficacy of an intervention with computers games based on the working memory and attention for a cognitive performance training of elementary school students. The sample was constituted by 42 students with average age of 10,43 years old (SD=1,23), with 22 male participants and 20 female participants. We used to evaluate the sleep with the parents a sleep questionnaire, a sleep diary and the Sleep Behavior Questionnaire. In regard to intervention, the subjectives were distributed in an experimental and in a control group, both with 21 participants. In the first group occurred the intervention that consisted in the working memory and attention training with two cognitive tasks (Safari e Brain Workshop) during 30 daily minutes, for a 6 weeks period. In an equal period, the students from the control group should reproduce an artwork using drawing software. To evaluate the cognitive performance we applied before and after the intervention period the Wechsler Intelligence Scale for Children (WISC-III). The results showed that in both the groups the performance of the intelligence, working memory, attention and visuospatial skills was below of the mean. The cognitive processes evaluated after of intervention in the experimental group had a performance significantly higher in the Perceptual Reasoning Index (t = -6,24; p < 0,01) and in the Full Scale IQ (t = -5,09; p < 0,01) and Performance IQ (t = -6,52; p < 0,01), suggesting a improvement on the visuospatial skills, attention, working memory and processing speed. On the control group, the performance was significantly higher in the Coding subtest (t = -5,38; p< 0,01) and in the Perceptual Reasoning Index (t = -3,66; p = 0,01), suggesting a improvement on the visuospatial skills and attention. The mean obtained with the Sleep Behavior Questionnaire was 53,76 (SD=14,96) for an experimental group and 61,19 (SD=12,82) for a control group, indicating tendency for a bad sleep quality in that last one. Not only during the first days, but also in the last fifteen days of the intervention we verified in the two groups an adequate time to sleep, duration and regularity, in the weekdays and on the weekends. We didn t find significant differences between the two groups in none of the sleep variables. We verified statistically meaningful improvement on the performance of the experimental group with the intervention in the two games. We didn t verify significant correlations between the games performance index and in the sleep variables of the experimental group individuals. We verified significant correlations among the performance on the Brain Workshop and the Cubes subtest, the Perceptual Reasoning Index and the Scale Performance IQ, suggesting that the significant improvement of the visuospatial skills and of the attention was correlated with the performance in the Brain Workshop. Although the absence of correlations with the performance in the Safari, possibly it also has relieved in the improvement of the cognitive performance. The findings support the hypothesis that the computer games might be a satisfactory tool for the improvement of the performance in visuospatial skills and attention. This can be resulted of the insertion of visuospatial stimulations in the task, for example, graphical elements with thematic for children that increase the interest. The IQ below mean the individuals might have influenced the improvement absence on the cognitive processes like the working memory with games. Moreover, it wasn t verified a relation between the sleep quality and the intervention efficacy. It might have been influenced by the n of the sample. Future studies must focalize in the improvement of the effect of the interventions with games